MACAM TIPE KEGIATAN BERBICARA DALAM "BUKU BAHASA INGGRIS" UNTUK SEKOLAH KEJURUAN PARIWISATA DI RUTENG - Yosefina Helenora Jem; Ely H. Selamat; Raymundus Beda; Helena Saimun (Jurnal Pendidikan dan Kebudayaan Missio, 2021)
The use of textbooks as a media in teaching learning processes especially in English Language Teaching cannot be denied. That’s why this present study is intended to investigate types of speaking activities presented in buku Bahasa Inggris for Tourism Vocational High School. The content of an English text book was described and analyzed by using a descriptive qualitative method. Buku Bahasa Inggris kelas X had been chosen as the source of data. The collected data were analyzed through some steps such as (1) classifying the data into types of speaking activities (Acting from Script, Communication Games, Discussions, Paper Talk, Questionnaires, Simulation and Role Play) and (2) identifying the dominant type of speaking activities. The result indicates buku Bahasa Inggris Kelas X contains six types of speaking activities and it is dominated by speaking activity of prepared talk